Rate-Distortion-Perception Tradeoff of Variable-Length Source Coding for General Information Sources - Matsumoto, Ryutaroh (arXiv.org, 2018)
Blau and Michaeli recently introduced a novel concept for inverse problems of signal processing, that is, the perception-distortion tradeoff. We introduce their tradeoff into the rate distortion theory of variable-length lossy source coding in information theory, and clarify the tradeoff among information rate, distortion and perception for general information sources. We also discuss the fixed-length coding with average distortion criterion that was missing in the previous letter.